2014
DOI: 10.1097/ftd.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Concentration-Controlled Mycophenolate Mofetil in Proliferative Lupus Nephritis

Abstract: Lupus nephritis patients induced with concentration-controlled MMF had excellent renal response and fewer adverse events with lower than usual dosing. MPA exposure had high interpatient variability, requiring measurements for personalized dosing, and fewer adverse events. Long-term cost reduction is achievable with lower doses and good renal response in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…Moreover, high between-patient variability in MPAshortened AUC was observed with extremes of 5.69 and 50.05 μg•h/mL•g (CV% of 53.5%) as well as 37.97 and 590.5 ng•h/mL•g (CV% of 63.8%) for dose-normalized total and free MPA AUC 0-2 , respectively. It is in accordance with other pharmacokinetic studies carried out in LN [2,7,20]. Recently, Abd Rahman et al [2] reported CV% of 50% and 53% for dose-normalized total and free MPA AUC 0-12 , Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, high between-patient variability in MPAshortened AUC was observed with extremes of 5.69 and 50.05 μg•h/mL•g (CV% of 53.5%) as well as 37.97 and 590.5 ng•h/mL•g (CV% of 63.8%) for dose-normalized total and free MPA AUC 0-2 , respectively. It is in accordance with other pharmacokinetic studies carried out in LN [2,7,20]. Recently, Abd Rahman et al [2] reported CV% of 50% and 53% for dose-normalized total and free MPA AUC 0-12 , Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The official TDM recommendations for MMF in LN are lacking, thus PK parameter being the best predictor of MPA exposure is still to be established. Nevertheless, contrary to the renal transplant recipients due to better kidney function observed in autoimmune diseases [21,22], in a number of PK studies conducted in non-transplant patients a significant correlation between total MPA C 0 and MPA AUC 0-12 was reported (r = 0.545 [23], r = 0.561 [20], r = 0.578 [21], r = 0.643 [2], r = 0.79 [24], r = 0.90 [6], r = 0.94 [22]). The recent retrospective study that evaluated the relationship between total MPA C 0 and AUC 0-4 has also reported significant correlation (r = 0.55) [25].…”
Section: Discussionmentioning
confidence: 90%
“…Median as well as mean dose-normalized values of MPA C trough and AUC 0-12 in our study were similar or slightly higher than in adult renal transplant recipients (Engelbertink et al, 2002;Kuypers et al, 2003;Shaw et al, 2004;Tedesco-Silva et al, 2005). On the other hand, median and mean dose-normalized MPA C trough and AUC 0-12 in our study were higher than those obtained in patients with lupus nephritis (Abd Rahman et al, 2015;Alexander et al, 2014).…”
Section: Discussioncontrasting
confidence: 64%
“…These findings are in accordance with the other review in LN whose authors suggested potential target level of MPA AUC 0-12 h between 35 and 45 mg$h$L 21 . 33 The discrepancy regarding the recommended lower limit of MPA AUC 0-12 h is because of the most recently published study by Alexander et al 10 The finding that MPA AUC 0-12 h $30 mg$h$L 21 was associated with a greater renal response at 1 year adds, by this study, to the general knowledge regarding LN. Although no upper limit for the MPA AUC 0-12 h target range has been determined so far in LN, the possibility to adjust the lowest …”
Section: Correlation Between Mpa Pharmacokinetics and Renal Response mentioning
confidence: 58%
“…It is worth mentioning that the main limitation of the majority of the studies, 10,11,[27][28][29][30][31] with exception of the study conducted by Zahr et al, 9 is the small sample size that ranges from 5 to 34 patients. Moreover, although free MPA fraction is pharmacologically active, none of the studies conducted so far has determined the free fraction of MPA.…”
Section: Correlation Between Mpa Pharmacokinetics and Renal Response mentioning
confidence: 97%